An Assessment of Gender stereotypes and messages contained in Zulu traditional wedding songs – A Case Study of the Mandeni Community - Zinhle Primrose Nkosi; Alexandra O’Neil; Rejoice Lindiwe Gugu Cele; Silindile Nonkululeko Thethwayo (E-Journal of Humanities, Arts and Social Sciences)
Traditional wedding songs provide a source of entertainment to wedding attendees while communicating messages. However, some songs depict problematic themes, including references to negative stereotypes about men and women in marriages. The primary purpose of this paper was to investigate messages contained in isiZulu wedding songs in Mandeni, KwaZulu-Natal province, South Africa. Secondly, it investigated the gender stereotypes contained in isiZulu wedding songs. This study used qualitative case study methods, under the interpretive paradigm. Twenty Zulu traditional wedding songs are used in the analysis. The Oppression Concept was used as a theoretical framework. The study revealed that some Zulu wedding songs contain messages that are intimidating to the youth and women, as they portray and endorse challenges that women face once they are married. This study also illuminated the gender stereotypes found in these songs, such as the portrayal of an unfaithful and abusive husband, female dependence on men for survival, obligatory submission of wives to husbands, and the normalisation of abuse from in-laws. The study concluded that Zulu wedding songs have the potential to discourage the youth from entering into marriages. The study recommended that young members of the Zulu communities and wedding participants should be discerning in which songs they sing, instead opting to sing the traditional wedding songs that do not contain gender stereotypes or recomposing The analysis of Zulu wedding songs is necessary to balance the constructive and destructive impact of these songs, that sections of the songs should better reflect modern Zulu values that support the liberation of women.